Beyond later and less marriage in Asia: reflections on Gavin W. Jones' contributions to the scholarship on marriage - McDonald, Peter; 2024; Utomo, Ariane (Asian Population Studies, 2024)
In this paper, we pay tribute to the late Emeritus Professor Gavin W. Jones and his outstanding contributions to the scholarship on marriage. Following a chronological assessment of his large body of work on marriage, we reflect on Gavin's general approach to research changing marriage patterns within and across diverse regions of Asia. His approach to studying marriage went beyond the conventional demographic focus on examining shifts in age at first marriage. He showed how examining shifting patterns across different, yet interrelated aspects of marriage offered an important window to understand the broader complexities of economic and socio-political change in the region; showing why there is much more to demography beyond counting births, deaths, and migration. As two generations of demographers, we reflected how his work and approach to research continue to influence our research and engagement with the region. Gavin's legacy extends beyond demography and Indonesian/Malay studies.
Keywords: Asia; Development; Divorce; Fertility; Gavin Jones; Marriage